KAJIAN DAMPAK PENCEMARAN LOGAM BERAT DI DAERAH SEKITAR LUAPAN LUMPUR SIDOARJO TERHADAP KUALITAS AIR DAN BUDIDAYA PERIKANAN - Sri Samsundari; Ima Yudha Perwira (Jurnal Gamma, 2011)
Sri Samsundari1 & Ima Yudha Perwira21Staf Pengajar & 2Alumni Jurusan Budidaya Perairan, Fakultas Pertanian-PeternakanUniversitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas 246 MalangEmail: srisamsundari@umm.ac.idABSTRACTSidoarjo as one potential area of aquaculture ponds very wide. Aquaculture sector can contributelarge revenues for Sidoarjo regency, but with the emergence of mudflow case PT. Lapindo led to adecline in production in the aquaculture sector. One of the factors that can affect the productiondecline is the pollution of mudflow PT. Lapindo, which is heavy metal. The purpose of this studywas to conduct a study of the impact of the mudflow events in the District Sidoarjo for aquacultureactivities. Samples were tested heavy metal content in this study is the gill and shrimp meat andpond water samples and water reservoir. While heavy metals identified are lead (Pb), Mercury (Hg),Copper (Cu) and cadmium (Cd). Observations on heavy metal content of pond water samples andorgan gill and shrimp meat showed a relatively high number compared with the water quality standardfor production and consumption. In the area range first (5 km), the highest heavy metal contentsare shown in black tiger shrimp gill samples, the 0255 ± 0029 ppm (Lead), 0142 ± 0041 ppm(Mercury), 0694 ± 0048 ppm (Copper) and 0035 ± 0007 ppm (Cadmium). While in the area of thesecond range (10 km), the metal content highest weight indicated on the shrimp gill samples, namely0124 ± 0009 ppm (Lead) 0089 ± 0018 ppm (Mercury), 0356 ± 0013 ppm (Copper) and 0023 ±0004 ppm (Cadmium). In the third range area (15 km), similar results are shown in sample Gill 0049± 0007 ppm (Lead), 0062 ± 0015 ppm (Mercury), 0091 ± 0018 ppm (Copper) and 0019 ± 0006ppm (Cadmium). The farther the distance from the center spurt pond, the less content heavy metalswas observed. However, the heavy metal content has been identified the majority of the area wasalso the third range has exceeded the water quality standard as well as production for consumptionexcept Lead (Pb) and Cadmium (Cd) on samples of pond water and mercury (Hg) in the samplesgills and shrimp meat.Keywords: heavy metals, aquaculture, shrimp